Central aortic systolic pressure and biochemical profile of young hypertensives in rural Malaysia - Abdullah, Aszrin; Abdul Razak, Tariq; Mohd Noor, Noriah (2010)
Hypertension is being identified in younger population. The prevalence of hypertension in Malaysia is 42.6% which contributes to the rising incidence of cardiovascular disease. The objective of the study is to assess the central aortic systolic pressure (CASP) and cardiovascular risk profile to young hypertensives in rural Malaysia. A total of 484 subjects were screened at a primary health care clinic in Kuantan, Malaysia. 97 subjects between the ages 20 and 40 with systolic and diastolic blood pressure ranges 120-159 mmHg and 80-99 mmHg respectively and age-matched were enrolled into a group cross-sectional, observational study. The cardiovascular risk-factor profile and CASP was assessed and compared in both groups. A total of 57 subjects and 40 controls were enrolled. The mean age were 32.74 ± 5.78 versus 31.05 ± 5.45 years (p=0.151), mean values for arterial pressure 102.10 ± 7.37 versus 82.24 ± 6.11 mmHg (p<0.001), total cholesterol 5.82 ± 0.96 versus 5.46 ± 0.97 (p=0.076), low-density lipoprotein 3.73 ± 0.86 versus 3.28 ± 0.86 (p=0.015), fasting blood sugar 4.67 ± 0.75 years versus 4.35 ± 0.42 (p=0.013), body mass index 28.72 ± 5.24 versus 23.18 ± 3.96 (p<0.001) and CASP 122.83 ± 9.58 versus 100.28 ± 6.94 mmHg (p<0.001). In conclusion, both the cardiovascular risk factor profiles and the CASPs were significantly higher in young hypertensives compared to age-matched controls.